(untitled) (Research, Society and Development, 2021)
The aim of this study was to assess whether there are benefits in telemonitoring post-chemotherapy symptoms with mobile devices compared to the traditional model of interval medical visits in the care of cancer patients, in order to provide gains in priority outcomes for the patient. This is an integrative review of articles published in Pubmed and Scielo in the last five years. Search terms included cancer, neoplasm, neoplasms, oncology, medical oncology, cancer care facilities, oncology service, telemedicine, telemonitoring, teleoncology, mobile health, mhealth, m-health, e-health, ehealth, video game, mobile game, mobile app, app-technology, chemotherapy, drug therapy, treatment, drug therapy. Randomized and controlled studies, published in English, cancer patients exposed to chemotherapy, remotely supervised from chemotherapy-induced acute toxicities, with data entered by mobile devices, were included. For data extraction, two reviewers used a form with standardized information fields. The studies analyzed after eligibility criteria point to better control of symptoms and outcomes. It is concluded that telemonitoring post-chemotherapy toxicity through mobile devices provides better symptom control and reduces complications.